Respuesta :
Answer:
33
Step-by-step explanation:
We can plug in the values for a and c
[tex]6(5)-(-3)[/tex]
[tex]30-(-3)[/tex]
[tex]=33[/tex]
Therefore, the value of the expression is 33.
#LearnWithBrainly
Answer:
33
Step-by-step explanation:
Given values:
- a = -3
- c = 5
1. Substitute the values in the expression
[tex]\implies 6c - a[/tex]
[tex]\implies 6(5) - (-3)[/tex]
2. Simplify the expression
[tex]\implies 6(5) - (-3)[/tex]
[tex]\implies 30 - (-3)[/tex]
[tex]\implies 30 + 3[/tex]
[tex]\implies 33[/tex]